Effects of α subunit substitutions on the oxidation of βCys93 and the stability of sickle cell hemoglobin - Wayne Hicks; Fantao Meng; Tigist Kassa; Abdu I. Alayash (Taylor & Francis Group, 2020)
The β subunit substitutions, F41Y and K82D, in sickle cell hemoglobin (Hb) (βE6 V) provides significant resistance to oxidative stress by shielding βCys93 from the oxidizing ferryl heme. We evaluated the oxidative resistance of βCys93 to hydrogen peroxide (H2O2) in α subunit mutations in βE6 V (at both the putative and lateral contact regions) that included (1) αH20Q/βE6 V; (2) αH50Q/βE6 V; (3) αH20Q/H50Q/βE6 V; (4) αH20R/βE6 V; and (5) αH20R/H50Q/βE6 V. Estimation by mass spectrometry of irreversible oxidation of βCys93 to cysteic acid (CA) was unchanged or moderately increased in the single mutants harboring a H20Q or H50Q substitution when compared to control (βE6 V). The introduction of Arg (R) singularly or in combination with Q enhanced the pseudoperoxidative cycle by slightly decreasing the ferryl in favor of ferrous and ferric species after treatment with H2O2. Higher rates for heme loss from the ferric forms of the Q species to the receptor high affinity recombinant apomyglobin were observed in contrast to the R mutants and control. Because of their improved solubility, a combination of Q and R substitutions together with mutations carrying redox active variants (F41Y/K82D) may provide dual antioxidant and antisickling targets in the design of gene therapy-based candidates.